AlGaN/GaN-HEMT power amplifiers with optimized power-added efficiency for X-band applications - Kühn, Jutta (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2011)
This work has arisen out of the strong demand for a superior power-added efficiency (PAE) of AlGaN/GaN high electron mobility transistor (HEMT) high-power amplifiers (HPAs) that are part of any advanced wireless multifunctional RF-system with limited prime energy. Different concepts and approaches on device and design level for PAE improvements are analyzed, e.g. structural and layout changes of the GaN transistor and advanced circuit design techniques for PAE improvements of GaN HEMT HPAs.